16.6k views
4 votes
3x-4y=1 and x=2y+1 using substitution

User Frhack
by
4.8k points

1 Answer

1 vote

Answer:

x =-1

y =-1

Explanation:

to solve this system of equation, using substiution method

3x-4y=1 ........................ equation 1

x=2y+1 ............................ equation 2

subbstitute for x into equation 1

3x-4y=1 ........................ equation 1

3(2y + 1) - 4y = 1

6y + 3 -4y = 1

2y + 3 = 1

collect the like terms

2y = 1- 3

2y= -2

divide both sides by the coefficient of y which is y

2y/2 = -2/2

y = -1

put the value of y =-1 into equation 2

x=2y+1 ............................ equation 2

x = 2(-1) + 1

x = -2 + 1

x = -1

therefore x =-1 y = -1

User Amberlynn
by
5.4k points